Securing Cloud-Native Applications: A Comprehensive Guide to Modern Challenges and Solutions - Prashant Chaturvedi, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
Cloud-native architecture has fundamentally transformed enterprise technology landscapes, introducing complex security challenges that traditional approaches struggle to address. This technical article examines the evolution of cloud-native security, focusing on container vulnerabilities, service mesh complexity, and resource configuration management. The article explores emerging solutions, including zero-trust architectures, automated security controls, and advanced observability frameworks. Through analysis of implementation case studies and industry research, the article demonstrates the effectiveness of AI-driven security automation, continuous monitoring, and integrated security practices in modern cloud environments. The article highlights the critical importance of comprehensive security frameworks specifically designed for cloud-native architecture while providing actionable insights for organizations transitioning to advanced security implementations.
Keywords: Cloud-native security; Zero-trust architecture; Security automation; Container security; Security observability; Service mesh; Remote cloud configuration management